Dimensions of economic theory and policy : essays for Anjan Mukherji - Mukherji, Anjan; Dastidar, Krishnendu Ghosh; Mukhopadhyay, Hiranya; Sinha, Uday Bhanu (New Delhi : Oxford University Press, 2011)
Contributed articles.
Oxford scholarship online Economics and Finance
Includes bibliographical references.
roy
Keywords: Economic policy; Economics